Assessment of Causes And Conditions of Making A Medical Error From Viewpoint of Nurses - Fatma Er; Serap Altuntaş (Association of Nurse Managers, 2017)
INTRODUCTION: Medical errors are an important is you for all health professionals. Nowadays medical errors have been derived various problems. Health professionals have played an important role in determination and prevention of these errors. Aim of in this study to assessment of causes and conditions of making a medical error from viewpoint of nurses. METHODS: The population of the descriptively study includes (n: 277) nurses employed in Public Hospitals (Bingöl State Hospital and Maternity and Children Hospital) in Bingöl city center. (n: 131) Nurses who all accepted to participate were selected for this study without carrying out any sampling method. The data were collected between November - December 2014 by using a questionnaire consisting of questions to determine nurses' personal and professional characteristics and their status and causes of medical errors. Both ethics committee and organization approval have taking for research. The data were calculated by use of a SPSS 16.0. RESULTS: It also became evident that most of the nurses did not perform any medical error before (77.9%), they did not witness any medical error by the other nurses (63.4%). Furthermore, nurses reported that major causes of medical errors were fatigue (78.6%), workload density (75.6%), over working hours and long working hours (74.8%), inexperience (72.5%), stress (71%) and inadequate professional knowledge (69.5%). DISCUSSION AND CONCLUSION: In the study, it became evident from the nurses' statements that nurses are attentive not to perform medical error during their professional practices.